(untitled) (Theatrum historiae, 2012)
Secondary school teachers in the Habsburg Empire in the second half of the 19th century ranked among those with an academic education and were usually state employees. Society respected their work but in most cases they came from a very limited group of men. P. Robert Christian Riedl was a Benedictine monk from Broumov. At the time he represented the still existing but no longer dominating model of a Roman Catholic priest who at the same time was an active educator at public secondary schools. He ended his career as a provincial school inspector. He belonged to the German language environment.